1982
DOI: 10.1002/j.0022-0337.1982.46.9.tb01580.x
|View full text |Cite
|
Sign up to set email alerts
|

Faculty retention in dental hygiene programs

Abstract: This study assesses the extent to which faculty turnover in dental hygiene programs is related to the type of educational institution. A questionnaire was mailed to 201 dental hygiene program directors; 17 5 responded (87 percent). Nearly 47 per‐cent of the directors associated with programs in state colleges and universities indicated they had experienced some degree of difficulty retaining faculty in the past five years; less than 18 percent of those in community colleges and technical schools experienced si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The research on those who resign suggests that faculty members depart for better salary (Ley, 1982;Weiler, 1985;Rausch, Ortiz, Douthitt, & Reed, 1989;Matier, 1990), for better relations within the department or with departmental leadership (Ley, 1982;Rausch, et al, 1989;Matier, 1990;Johnsrud & Heck, 1994)) and for personal reasons (Ley, 1982;Weiler, 1985), such as quality of life issues (Johnsrud & Heck, 1994) and issues surrounding the employment of one's spouse or partner (Rausch, et al, 1989). Although not mentioned in all articles, two studies (i.e., Weiler, 1985;Matier, 1990) found funds for research and opportunity to do research to be important.…”
Section: Research On Those Who Resignmentioning
confidence: 99%
“…The research on those who resign suggests that faculty members depart for better salary (Ley, 1982;Weiler, 1985;Rausch, Ortiz, Douthitt, & Reed, 1989;Matier, 1990), for better relations within the department or with departmental leadership (Ley, 1982;Rausch, et al, 1989;Matier, 1990;Johnsrud & Heck, 1994)) and for personal reasons (Ley, 1982;Weiler, 1985), such as quality of life issues (Johnsrud & Heck, 1994) and issues surrounding the employment of one's spouse or partner (Rausch, et al, 1989). Although not mentioned in all articles, two studies (i.e., Weiler, 1985;Matier, 1990) found funds for research and opportunity to do research to be important.…”
Section: Research On Those Who Resignmentioning
confidence: 99%
“…Breslow's study, on the other hand, showed that some faculty moved for personal reasons, unsupported working environments, and holding better positions (8). Lee (1982) also found in his study that the attrition of faculty for personal reasons, job dissatisfaction, and low salary at the state universities was slightly higher than that of the schools of social and technical sciences (9).…”
Section: Introductionmentioning
confidence: 98%
“…Breslow's study, on the other hand, showed that some faculty moved for personal reasons, unsupported working environments, and holding better positions [8]. Lee (1982) also found in his study that the attrition of faculty for personal reasons, job dissatisfaction, and low salary at state universities was slightly higher than that of the schools of social and technical sciences [9]. Nonetheless, structured programs seem to be effective in faculty development, while motivating and enhancing the quality of students' learning and progress, leads to the retention of faculty.…”
Section: Introductionmentioning
confidence: 99%